Descriptive Study to Assess the Knowledge Concerning Bio-medical Waste Handling Among B.Sc. Nursing Scholars of Selected Nursing Colleges of District Kangra (H.P) - Bharti Rana; Meenakshi Pathania (International Journal of Biomedical Innovations and Engineering, 2023)
The waste generated from health actions can be dangerous, poisonous, toxic and even mortal because of their high probable for ailment transmission and injury that also outcome in environmental disturbances. The first step to safe disposal of dangerous hospital wastes. an acceptable and proper knowledge of Bio Medical Waste Management among the students of Nursing is important. Appropriate managing of health care waste is then a vital part of environmental health protection, and it should be considered out to be an integral step of health care services. Aim: To assess the knowledge regarding bio- medical waste procedure among b.sc nursing scholars. Methods: A descriptive cross-sectional study, was administered. The study was conducted in netaji Subhash college of nursing, h.p. The purposes of this study were to find the extent of knowledge regarding BMW procedure among the nursing scholars, The sampling technique non-probability was used and a semi-structured questionnaire to check the knowledge regarding Bio-medical waste management was administered. SPSS interpretation 20 was used for analysis. Conclusion: The study report shows that among 100 nursing scholars, the nearly (71.67%) 71.67% repliers was having good knowledge, among 23.33% of nursing scholars was having poor level of knowledge and among 5% nursing repliers was having fair level of knowledge regarding BMW procedure.
Keywords: Knowledge and Biomedical Waste procedure; Nursing Scholars; disposal; environmental disturbances; health care waste